A novel PCOS rat model and an evaluation of its reproductive, metabolic, and behavioral phenotypes. (2nd October 2021) - Kamada, Shuhei; Yamamoto, Yuri; Aoki, Hidenori; Tamura, Kou; Takeda, Asuka; Minato, Saki; Masaki, Rie; Yanagihara, Rie; Hayashi, Noriko; Yano, Yuya; Imaizumi, Junki; Kagawa, Tomohiro; et al.
Abstract: Background: Although animal models of PCOS have been used in many studies, none of them can reproduce both the reproductive and metabolic phenotypes of PCOS. In addition, behavioral parameters have not been evaluated in PCOS animal models. Purpose: We tried to produce an improved rat model of PCOS, and the reproductive, metabolic, and behavioral phenotypes of the model rats were evaluated. Methods: Female rats were implanted with silicon tubes containing oil‐dissolved dihydrotestosterone (Oil‐DHT) as a new PCOS model. Their phenotypes were compared with those of conventional PCOS model rats (DHT), into which tubes containing crystalline DHT were implanted, and non‐DHT‐treated rats (control). Results: Both the Oil‐DHT and DHT rats showed greater body weight gain, food intake, and fat depot weight than the control rats. Furthermore, these groups showed fewer estrous stages and increased numbers of cystic follicles. The DHT rats exhibited lower ovarian and uterine weights than the control rats, whereas no such changes were observed in the Oil‐DHT rats. The Oil‐DHT and DHT rats showed less locomotor activity in the light phase than the control rats. Conclusions: Our proposed PCOS model reproduced both the reproductive and metabolic phenotypes of PCOS and may have potential for PCOS research.